A network approach to full core temperature analysis in advanced nuclear heat-pipe systems. (15th September 2021) - Mueller, Cole; Tsvetkov, Pavel
Highlights: A network analysis method was developed. Full core resolution is possible with this method very inexpensively. The method was benchmarked against OpenFOAM on representative geometries. Accuracy within 1% was demonstrated for a novel geometry. Accuracy within 7% was demonstrated for a standard geometry. Abstract: Advanced heat-pipe systems are becoming more popular for micro-grid applications globally. With this increase in interest, methods for rapid analysis of the system are necessary for quick design iterations. The method proposed is bench marked against an OpenFOAM conduction approximation for two reactor like geometries. One geometry is a more traditional approach and the other geometry is a novel approach. The method is designed to rapidly attain heat-pipe power throughput to compare with characteristic limits of the heat-pipe design. For the traditional geometry the predicted peak temperatures were within 7% of the OpenFOAM solutions and the novel geometry is within 1% of the OpenFOAM solution giving high confidence that this can be used to rapidly evaluate and analyze new core geometries.